Tuakana-teina peer education programme to help Māori elders enhance wellbeing and social connectedness - Oetzel, John G.; Simpson, Mary; Meha, Pare; Cameron, Michael P.; Zhang, Yingsha; Nock, Sophie; Reddy, Rangimahora; Adams, Hariata; Akapita, Ngapera; Akariri, Ngareo; Anderson, Justina; Clark, Marama; et al. (BMC geriatrics, 2024)
Background There are significant inequities between Māori (Indigenous people) and non-Māori in ageing outcomes. This study used a strengths-based approach based on the key cultural concept of mana motuhake (autonomy and self-actualisation) to develop a tuakana-teina (literally older sibling-younger sibling) peer education programme to assist kaumātua (elders) in addressing health and social needs. The purpose of this study was to test the impact on those receiving the programme. Three aims identify the impact on outcomes, resources received and the cost effectiveness of the programme. Methods Five Kaupapa Māori (research and services guided by Māori worldviews) iwi (tribe) and community providers implemented the project using a partnership approach. Tuakana (peer educators) had up to six conversations each with up to six teina (peer learners) and shared information related to social and health services. A pre- and post-test, clustered staggered design was the research design. Participants completed a baseline and post-programme assessment of health and mana motuhake measures consistent with Māori worldviews. Open-ended questions on the assessments, five focus groups, and four individual interviews were used for qualitative evaluation. Findings A total of 113 kaumātua were recruited, and 86 completed the programme. The analysis revealed improvements in health-related quality of life, needing more help with daily tasks, life satisfaction, paying bills and housing problems. Qualitative results supported impacts of the programme on mana motuhake and hauora (holistic health) through providing intangible and tangible resources. Cost-effectiveness analysis showed that the intervention is cost effective, with a cost per QALY of less than the conventional threshold of three times GDP per capita. Conclusions A culturally-resonant, strengths-based programme developed through a participatory approach can significantly improve health and social outcomes in a cost-effective way. Trial Registry Clinical trial registry : Trial registration: (ACTRN12620000316909). Prospectively registered 06/03/2020, https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=379302&isClinicalTrial=False .